Perspectives on China's outward foreign direct investment - Morck, Randall; Yeung, Bernard; Zhao, Minyuan (Journal of International Business Studies, 2008)
Recent economic data reveal that, at the infant stage, China's outward foreign direct investment (FDI) is biased towards tax havens and Southeast Asian countries and are mostly conducted by state-controlled enterprises with government sanctioned monopoly status. Further examination of China's savings rate, corporate ownership structures, and bank-dominated capital allocation suggests that, although a surge in China's outward FDI might be economically sensible, the most active players have incentives to conduct excessive outward FDI while capital constraints limit players that most likely have value-creating FDI opportunities. We then discuss plausible firm-level justifications for China's outward FDI, its importance, and promising avenues for further research.